If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(9x + -8) = 43 Reorder the terms: 4(-8 + 9x) = 43 (-8 * 4 + 9x * 4) = 43 (-32 + 36x) = 43 Solving -32 + 36x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 36x = 43 + 32 Combine like terms: -32 + 32 = 0 0 + 36x = 43 + 32 36x = 43 + 32 Combine like terms: 43 + 32 = 75 36x = 75 Divide each side by '36'. x = 2.083333333 Simplifying x = 2.083333333
| W+-6w-7w=-18 | | -5-3y=-77+9y | | -14w+15w=11 | | 25+25+5q+5q+5q+5q= | | 2p+5p-2p=20 | | 15c-11c-3c=10 | | 29+6=-a-8 | | 3(y+7)=-9y-39 | | g-g+g+g=18 | | -24x+70=-2x^2 | | P-5/6=3/8 | | P-5/6=5/8 | | cos(2x)-senx=0 | | 9(z+5)=8(z-3)+z | | 29+6=a-8 | | 9-9+9+9=18 | | 4(b-80)+79=87 | | -3d+-d=16 | | 2(5(3))+2(6(3))=66 | | X+x+38=110 | | 29+6=a-9 | | 6a+2a-6a-2a+a=18 | | -3x+8x=6(x+2)-(x+12) | | 2(5x)+2(6x)=66 | | Y=go+m | | lnx+ln(x+6)=2 | | 2(5x)*2(6x)=66 | | -6(5n+7)=10n | | 4+3t-(3t+8)-(3t+6)= | | 4x+5=4(x-2) | | 4b-3s=24 | | 206=2l+2w |